Expression of Phytase gene in transgenic maize with seed-specific promoter 27-kDa γ Zein and constitutive promoter CaMV 35S - Ririn Septina Arthasari; Rani Agustina Wulandari; Panjisakti Basunanda (Jurnal Ilmu Pertanian, 2021)
Phytase enzymes are applied to animal feed to help animals absorb more nutrients. The use of feed raw materials containing phytase enzymes is expected to reduce the cost of animal feed production. Efforts to increase the phytase content in maize were carried out by improving genetics, in the way of assembling transgenic plants containing high phytase content. The 27-kDa γ Zein promoter is a specific promoter that expresses genes in caryopsis, and promoter CaMV 35S is a constitutive promoter that controls gene expression in all tissues and generally does not depend on the growth phase. Transgenic maize was transformed using Agrobacterium tumefacien infection method on maize B104. The reverse transcriptase polymerase chain reaction (RT-PCR) approach was used to examine the expression of phytase genes in leaves, roots, and caryopsis was done 10, 20, and 30 days after pollination (DAP). The phytase enzyme activity test was also carried out by using the colorimetric phosphomolybdate analysis method to see the phytase enzyme activity in unit µg-1. The results showed that the phytase gene in transgenic plants with the 27-kDa γ Zein promoter was highly expressed in maize caryopsis, but in line Z6.10 was also expressed in leaves, while in the CaMV 35S promoter the phytase gene was only expressed on the leaves. Phytase enzyme activity showed that transgenic maize was higher than non-transgenic maize.